HUTARI Program in Nutrition Intervention and Health Service Strengthening - Arifa Sofia Putri; Apolinus Silalahi; Muhammad Fajri Fitriyanto (Prospect Publishing, 2025)
Nutritional issues such as stunting remain a major challenge to child health in Hulonthalangi District. To address this, PT Pertamina Patra Niaga Integrated Terminal Gorontalo, through the Pertamina SEHATI program, initiated the HUTARI Program as a health and nutrition-based community empowerment effort. This program intervened with 36 stunted toddlers, provided nutrition education to 24 pregnant women and 55 mothers of toddlers, and trained 25 integrated health post (Posyandu) cadres to improve the capacity of local health services. Furthermore, service quality was strengthened through the optimization of medical equipment at one community health center (Puskesmas) and five sub-community health centers (Puskesmas Pembantu). Community participation was facilitated through coordination forums and joint training between cadres, health workers, and community leaders to ensure active involvement and program sustainability. Community awareness was measured through pre-post nutrition education surveys and observations of child feeding behavior. The results of the activities showed an increase in understanding and practice of balanced nutrition, family support for child growth and development, and strengthened health service capacity at the community level. This program demonstrates that multi-stakeholder collaboration and a participatory approach are key to accelerating sustainable stunting reduction